The Changing Dynamics of Higher Education Middle Management
XIV, 252 p.
Keywords: Known as either ‘soft’ or ‘hard’ ‘managerialism’, ‘new managerialism’ or ‘new public management’, this new narrative has, irrespective of moniker, permeated the institutions of higher education almost everywhere. Taking this as its context, this volume is founded on a comprehensive international comparative analysis of the evolving role of middle-level academic managers—deans, heads of department and their equivalents. The chapters address key questions that will determine the future of academe: have the imperatives of management theory caused a realignment of the values and expectations of middle-level academic managers? In what way do the new expectations placed on this group shape the academic profession as a whole? And, whose interests do middle-level academic managers represent? Based on material presented at one of the high-level Douro Seminars on research into tertiary education, this volume systematically combines theoretical views with empirical analysis. It argues that ‘managerialist’ pressure has resulted in changes in the way academic performance is measured. There has been a shift in criteria away from research reputation, teaching and scholarship to the measurement of performance based upon management capacities. This has given middle-level academic managers a pivotal role halfway between the predilections of high-level decision makers and the maintenance of academic values and control. The enhanced expectations and more defined functions of middle-level academic managers are in clear contrast to earlier times, when the position was considered a public-spirited rite of passage for career-minded academics. Despite this, the contributors to this book believe that the middle-level managers in the ten countries examined are neither corporate lackeys nor champions of academe. It is becoming increasingly clear that the ability of organisations to achieve their aims is largely dependent on the skill and dedication of middlemanagers. Past studies of organisational dynamics have been preoccupied with the executive level of management. This text, which will be of great interest to researchers and policy makers alike, attempts to redress the balance.